Deformations and seepage-induced erosion of fractured rocks in fault under confined settings - Wenbin SUN; Dianjin TIAN; Cheng MA; Yanchao XUE; Can YANG; Kaipeng ZHU (Meitian dizhi yu kantan)
ObjectiveMost of the mining areas in China have entered the deep mining stage. In this case, the risks of mine water inrushes increase significantly due to the complex deep hydrogeological conditions, a significant increase in the number of hidden disaster-causing factors, and the existence of faults. MethodsUsing a deformation-seepage experiment system for fractured rocks, this study investigated the characteristics of compressive deformations and seepage-induced erosion of fractured rocks in faults. By analyzing the impacts of particle-size distribution combinations, saturation state, and seepage pressure, on the deformation-permeability characteristics of fractured rocks under confined axial compression, this study investigated the time-varying patterns of changes in the particle erosion characteristics, void structure, and seepage parameters of the fractured rock samples. Results and Conclusions The results indicate that the peak strain of the fractured rock samples increased with an increase in the Talbot index (n). For samples with the same particle size distribution, those in the water-saturated state exhibited higher incremental strain than those in the dry state. The fitted curves of the lost mass of particles exhibited an exponential growth function with time, with the lost mass being inversely proportional to the confining axial stress. Meanwhile, the mass of secondary particles increased with the axial load. The evolutionary trend of the void rate of the rock samples was closely related to their particle size distributions, with the Talbot index (n) correlating positively with the overall void rate of the samples. Comparison before and after loading and seepage revealed that the fractal dimension (D) was inversely proportional to the value of n and the masses of fine and coarse particles increased and decreased, respectively. Furthermore, the fractal dimension of the rock samples increased significantly after loading and seepage. Macroscopically, the confined water lift within faults can be divided into the initial stage of water lift, the expansion stage of channels for discharging water and sand inrush, and the mature stage of the channels. Microscopically, the lift involves the soaking and softening, dislocation and compression, deformations and cracking, and fragmentation and detachment of rock masses. The findings of this study will provide experimental data and a theoretical basis for research on the evolutionary patterns of water inrush disasters in faults.